APPLICATION OF THE FOCUS GROUP METHOD IN PSYCHOLOGICAL EMPIRICAL RESEARCHES - Hovhannisyan, S.V. (Modern Psychology, 2025)
This article discusses one of the key issues of the psychological empirical research, specifically the possibilities of introducing the focus group method within the experimental research basic techniques. A fact is emphasized that, for researching separate issues in the contemporary phase of scientific knowledge, partial research methods are also combined with the special methods applied in empirical psychology, which are borrowed from other sciences. And since, among similar methods, the focus-group method progressively gaining an active use in psychological research is specially highlighted, an attempt has been made to detailedly introduce its application methodology.
Keywords: focus-group method; empirical research; methodology; in-depth interview; qualitative research; content analysis